Dr. Xie Yuxuan — Deep Plane Facelift — Taipei - Yuxuan, Xie (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Xie Yuxuan, practicing in Taipei, Taiwan. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003127; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; taiwan; taipei